Global energy justice : problems, principles, and practices - Sovacool, Benjamin K.; Dworkin, Michael H. (Cambridge : Cambridge University Press, 2014)
We need new ways of thinking about, and approaching, the world's energy problems. Global energy security and access is one of the central justice issues of our time, with profound implications for happiness, welfare, freedom, equity, and due process. This book combines up-to-date data on global energy security and climate change with fresh perspectives on the meaning of justice in social decision-making. Benjamin K. Sovacool and Michael H. Dworkin address how justice theory can help people to make more meaningful decisions about the production, delivery, use, and effects of energy. Exploring energy dilemmas in real-life situations, they link recent events to eight global energy injustices and employ philosophy and ethics to make sense of justice as a tool in the decision-making process. They go on to provide remedies and policies that planners and individuals can utilize to create a more equitable and just energy future.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Energy policy; Social justice